Demand for non-life insurance under habit formation - Li, Wenyuan (2022)
This paper studies the optimal non-life insurance for an individual exhibiting internal habit formation in a life-cycle model. We show that the optimal indemnity is deductible under the expected premium principle. Under the additional assumption of exponential utility functions, we obtain the optimal strategies explicitly and find that habit formation reduces insurance coverage. Our model offers a potential explanation for global underinsurance phenomenon. Some numerical examples and sensitivity analysis are presented to highlight our theoretical results.